Δ-matroid and jump system. Issue 2 (25th July 2005) - Kabadi, Santosh N.; Sridhar, R.
Abstract : The concept ofΔ -matroid is a nontrivial, proper generalization of the concept of matroid and has been further generalized to the concept of jump system. In this paper, we show that jump systems are, in some sense, equivalent toΔ -matroids. Using this equivalence and theΔ -matroid theory, we give simple proofs and extensions of many of the results on jump systems.